2020
DOI: 10.1002/lno.11640
|View full text |Cite
|
Sign up to set email alerts
|

Arctic crustose coralline alga resilient to recent environmental change

Abstract: Rising atmospheric carbon dioxide is warming Arctic seawater at a rate twice the global average due to multiple positive feedbacks. Thus, warming is disproportionately influencing data‐poor Arctic marine ecosystems. Subarctic flora are an important component of these ecosystems, along with the less biodiverse flora endemic to the Arctic. Warming will likely lead to an increasing dominance of subarctic flora that will be initially successful due to a shorter sea ice period. Benthic crustose coralline algae pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…compactum increase with increasing T. Although the present laboratory‐based study was conducted over shorter timescales, the results are consistent with those of Williams, Chan, Halfar, et al. (2021) across the T range that the wild samples in Williams, Chan, Halfar, et al. (2021) were evaluated (−1 to −7°C).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…compactum increase with increasing T. Although the present laboratory‐based study was conducted over shorter timescales, the results are consistent with those of Williams, Chan, Halfar, et al. (2021) across the T range that the wild samples in Williams, Chan, Halfar, et al. (2021) were evaluated (−1 to −7°C).…”
Section: Resultssupporting
confidence: 91%
“…Williams, Chan, Halfar, et al. (2021) found that, over multidecadal timescales, extension rates of C . compactum increase with increasing T. Although the present laboratory‐based study was conducted over shorter timescales, the results are consistent with those of Williams, Chan, Halfar, et al.…”
Section: Resultsmentioning
confidence: 99%
“…However, the general north‐south orientation of the continental shelf of the northeastern United States and southeastern Canada may permit northward retreat of C. compactum into colder waters along the Canadian continental shelf as temperatures warm. Analysis of historical skeletal growth, density, and calcification in wild collected C. compactum suggests that this species has been benefiting from a longer summer season and associated earlier spring sea ice breakup in the high Arctic (Williams et al., 2021). In contrast, the generally east‐west orientation of the Aleutian archipelago that supports large populations of C. nereostratum preclude such a northerly retreat into colder waters.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the biological and biogeochemical function of shallow water settings in the future will depend on the extent to which environmental changes favor pelagic or benthic primary production. Ongoing hydrological, physical, and biogeochemical changes appear to stimulate the northward migration and areal expansion of seagrass and macroalgae (Kortsch et al 2012; Krause‐Jensen et al 2020) and the growth of resilient crustose corallines (fundamental ecosystem engineers in deeper waters) (Williams et al 2021). Thus, predictions for the future Arctic need to better address the importance of benthic primary producers and the energy they provide for coastal food webs and constrain the regional variability in their response to ongoing environmental changes.…”
Section: Changing Ecology and Biogeochemistry In The Coastal Zone Out To The Open Oceanmentioning
confidence: 99%